(untitled) (Analysis of International Sciences, 2024)
Today in the day tourism industry high to indicators have being is going in Uzbekistan of tourism 3 main types available : input, output and internal tourism . Enter and internal to tourism main and special touristic products includes : touristic attention deserves to places excursions ; hotels, rest residences, spas, sanatoriums, tourism villages, home-camps, camps placement ; national dishes and wines taste to see festivals and holiday in events participation reach country across comfortable action